Adversus Iudaeos in the Sermon Written by Theodore Syncellus on the Avar Siege of AD 626 - Hurbanič, Martin (Studia Ceranea, 2016)
A sermon attributed to Theodore Syncellus (Theodoros Synkellos) is considered as one of the basic sources for the study of the Avar siege of Constantinople in AD 626. Therefore, the most historians paid more attention to the analysis of its historical background than to its ideological content. From the ideological point of view, the document serves as an evidence that a fear for the future of the Empire and its capital Constantinople began to rise within emerging Byzantine society. The Avar siege served its author mainly as a model for developing his polemics with imaginary Jewish opponents and their religion. It deserves to be included in a long succession of similar polemical treatises, which have existed in Christianity from its earliest times.